Diagnosis of fault brush winding stator induction motor using external sensor flux of three axes - Delfianti, Rezi; Afif, Yusrizal; Prahesti, Fidya Eka; Mustaqim, Bima; Silalahi, Bolas Boy (Institute of Advanced Engineering and Science, 2024)
This research investigates short-circuit problems in induction motor stators by constructing a motor with a changing winding and leaking flux data. The data is used to evaluate X, Y, and Z axes and map motor waves under normal and abnormal conditions. This study is expected to compare the effectiveness of the observation method from three different axes at the same motor condition to be further helpful in repairing induction motor damage caused by the circuit. From the results of the study, it shows that the harmonic value of the stator current will be more effective than the Y axis with a harmonic amplitude value of -38.8 dB, higher than the harmonic value of the current on the X axis with a difference of 33.89 dB and a difference of 0.32 dB from the Z axis. Suppose the disturbance is measured from the stray harmonic value. In that case, the flux will be more effective than the X axis with a harmonic amplitude value - 25.27 dB, higher than the harmonic value of the flux on the Y axis with a difference of 6.425 and a difference of 4.85 dB from the Z axis.